Trophic pyramids reorganize when food web architecture fails to adjust to ocean change - Nagelkerken, Ivan; Goldenberg, Silvan U; Ferreira, Camilo M; Ullah, Hadayet; Connell, Sean D (Science (American Association for the Advancement of Science), 2020)
As human activities intensify, the structures of ecosystems and their food webs often reorganize. Through the study of mesocosms harboring a diverse benthic coastal community, we reveal that food web architecture can be inflexible under ocean warming and acidification and unable to compensate for the decline or proliferation of taxa. Key stabilizing processes, including functional redundancy, trophic compensation, and species substitution, were largely absent under future climate conditions. A trophic pyramid emerged in which biomass expanded at the base and top but contracted in the center. This structure may characterize a transitionary state before collapse into shortened, bottom-heavy food webs that characterize ecosystems subject to persistent abiotic stress. We show that where food web architecture lacks adjustability, the adaptive capacity of ecosystems to global change is weak and ecosystem degradation likely.As human activities intensify, the structures of ecosystems and their food webs often reorganize. Through the study of mesocosms harboring a diverse benthic coastal community, we reveal that food web architecture can be inflexible under ocean warming and acidification and unable to compensate for the decline or proliferation of taxa. Key stabilizing processes, including functional redundancy, trophic compensation, and species substitution, were largely absent under future climate conditions. A trophic pyramid emerged in which biomass expanded at the base and top but contracted in the center. This structure may characterize a transitionary state before collapse into shortened, bottom-heavy food webs that characterize ecosystems subject to persistent abiotic stress. We show that where food web architecture lacks adjustability, the adaptive capacity of ecosystems to global change is weak and ecosystem degradation likely.